ANALYSIS OF COMPLIANCE TO THERAPY OF PATIENTS WITH BRONCHIAL ASTHMA (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
In this article, an analysis is conducted on the treatment and treatment regimen of patients with bronchial asthma, utilizing scientific sources. The analysis examines the factors that prevent patients from adhering to the treatment and regimen, as well as the reasons for their poor adherence. The results of such analyses have been generalized in various countries around the world.